TINGKAT KESIAPAN KOTA BANDARLAMPUNG DALAM MENERAPKAN KONSEP SMART MOBILITY - Ian Nico Panra Sinaga; Muhammad Irfan Affandi; Lutfi Setianingrum (Jurnal Perencanaan dan Pengembangan Kebijakan, 2021)
Nowadays, smart city becomes a promising program, because smart city offers good service to the government by involving information technology, which provides open space in public services. Bandar Lampung City Government is currently trying to make the city of Bandar Lampung become smart city. Movement that continues to occur, the more citizens and transportation problems in Bandar Lampung City, needs to be the application of the concept of smart mobility immediately, in applying the concept of smart mobility we must see how ready Bandar Lampung city in applying it, therefore we need to take one of the districts in bandar Lampung city. One of the sub-districts in Bandar Lampung city is Tanjung Karang Pusat Subdistrict which is one of the most populous sub-districts and also a center of trade and services. This research was conducted with qualitative approach, data analysis techniques using descriptive analysis and scale analysis. The research variables are drawn from the conclusions of smart city experts, research has already been done and precedents. From the results of the analysis that has been done the results of the research on the level of readiness of Tanjung Karang Pusat Subdistrict in applying the concept of smart mobility is quite ready.